Absence of Praxis, Absence of Progressivism: The Need for Pedagogical Praxis for Progressivist Educators - Harvey, Lyndze Caroline (Journal of the Canadian Association for Curriculum Studies, 2020)
This paper discusses the common philosophical orientation of both in-service and pre-service teachers in mainstream Canadian public schooling to progressivism. Although the meaning of progressivist theory in education varies, this paper explores a definition that encompasses the desire to teach self-governance and to prepare students for participating in a democratic and pluralistic society. Through a philosophical discussion, a deep reading of the literature and autoethnographic storytelling, this paper explores the ways in which in-service and pre-service teachers commonly define progressivist practice. They do this by juxtaposing progressivism to traditionalism without questioning theory-practice connections and disconnections through reflection and action. This leads to what I call bad praxis and a subversion of the aims of progressivist education because teachers are immersed in narratives that tell them to be politically neutral, that they are incapable of theorizing or philosophizing, and that critical discourse should be comfortable; good praxis gives the impression of being radical. However, progressivist connections to democracy are political; teachers can do more than tactfully cope in the classroom, and critical thinking is not only based in reason but also emotion. In my presentation, I make comparisons to Foucault’s (2008) concept of good and bad parrēsia, and much like the connection he makes between parrēsia and democracy, I argue that the ambiguity of praxis and the deterioration of praxis within progressivist teaching, leads to bad praxis and a failure to walk our progressivist talk. How can in-service and pre-service teachers develop good praxis skills and how might this shift support progressivist goals?